Republic of Belarus : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2001 Article IV Consultation highlights that the authorities in Belarus made headway in 2001 in further liberalizing the foreign exchange market and stabilizing the exchange rate and reducing inflation. They also took steps to liberalize prices and initiate other structural reforms. At the same time, a policy of raising wages to unaffordable levels during an election year undermined progress achieved in stabilization. Significant progress was achieved under a Staff-Monitored Program, covering April 1-September 30, 2001. Monetary/exchange rate policy was implemented successfully, and the benchmarks for structural reforms were largely met.